Liberalism without Democracy : Nationhood and Citizenship in Egypt, 1922-1936 - Maghraoui, Abdeslam (Book collections on Project MUSE., 2006)
This analysis of the failure of efforts to achieve liberal reform in Egypt following its independence from Great Britain in 1922 has implications for modern-day nation-building efforts in the Mideast.